Penatalaksanaan Pneumonia dengan Pendekatan Kedokteran Keluarga: Sebuah Laporan Kasus - Afrileo Vebi Eka Utama; Wianti Soeryani Soedjal; Veli Sungono (Medula, 2023)
Abstract Pneumonia is an acute inflammation of the lung parenchyma caused by microorganisms (bacteria, viruses, fungi, parasites, protozoa), not caused by Mycobacterium tuberculosis. Pneumonia has clinical symptoms such as fever, cough, shortness of breath, chest pain, ronkhi, wheezing and decreased breathing sounds. The diagnosis of pneumonia itself is based on anamnesis, physical examination, and supporting examinations such as laboratory tests and thoracic photographs. This case report applies a holistic and comprehensive family medicine approach and prioritizes patient centered, family focused and community oriented management. This case study was obtained through history taking, physical examination and home visits. This case report describes a 17-year-old male with clinical symptoms of pneumonia, namely fever, cough and shortness of breath with laboratory examination found leukocytosis and radiology obtained infiltrates in both lungs with the impression of pneumonia. In this case, comprehensive management has also been carried out, namely patient centered, family focused and community oriented.